Comparison of Vestibular Function Between Right and Left Handed Normal Population - Bhandari, Sharma; Shrestha, Sagun; Saxena, R.K. (Journal of Nepalgunj Medical College, 2018)
Objective To identify the side of vestibular dominance in right handed & left handed people.Method A total of 50 normal subjects, aged between 15 - 45 years were included as Left handers (n = 25) and Right handers (n = 25). Handedness was confirmed by the Annett Hand Preference Questionnaire. Bithermal caloric testing was done which was recorded by Electronystagmography (ENG). Maximum Slow Phase Velocity (MSPV) was taken as the parameter of choice. Directional Preponderance (DP) and Canal Paresis (CP) were calculated in each group.Results Out of the 25 Left handed subjects, 8 had DP towards Left whereas 7 had DP towards the Right and the remaining 10 showed no DP to any side (normal) (p